Notices of two ancient Graves recently opened in the vicinity of Dunrobin Castle, Sutherlandshire (Proceedings of the Society of Antiquaries of Scotland, 1855)
Report on two graves that were opened by Dr. J. J. Ross. The report firstly covers one of the graves' dimensions and decorations as well as its contents. After examining this grave, the archaeologist was then able to uncover another similar grave nearby. The bones from these graves were exhibited at the Society. It was speculated that these graves may have been of Scandinavian origin.